Social Impact Investing Beyond the SIB Evidence from the Market (Palgrave Studies in Impact Finance,, 2018)
This book provides a preliminary attempt to understand the impact investors' preferences and characteristics. It offers an empirical insight of the main features characterizing social risk of Social Impact Bonds (SIBs) and explores the correlation existing between social risk and financial return. It assesses case studies of social impact investment architectures and their legal and operational limits. It also analyzes new trends in social impact measurement, focusing on the Spanish and Swedish experiences. The book concludes with a road map of priorities and policy strategy for social impact investments development.